IDENTIFIKASI SENYAWA YANG BERKORELASI TERHADAP RASA PAHIT SELAMA PERKEMBANGAN FASE BUAH MELON (Cucumis melo L.) KULTIVAR GAMA MELON PARFUM - ANTO, ANTO ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The Cultivar Melon-Gama Melom Parfum (GMP) is new product of cultivar melon made by crossing between the brood of melon ♀NO3 and ♂MK5 which has a fenotipe character that its very fragrant like parfume, the weight is around 300-500 gram, it has the oblate shape, the colour is olive with an unique ornament curved the line long side, flesh fruit is white, it does not have any “net“ and the taste is bitter. This GMP melon has the fragrant aromatic but it’s taste bitter, with the result that makesan identification of some compoundwich has the correlation with the bitter taste during the expansion of melon GMP, such as calcium mineral, free amino acids, and total phenolic content. This research was analysis the compounds which is predicted has correlation with the bitter taste, that’s calcium mineral, free amino acid, and total phenolic content from each expansion phase of the fruit the age 1 – 5 weeks. The analysis of the calcium mineral by AAS ( Atomic Absorption Spectrophotometric) instrument, amino acid by HPLC, and total phenolic content by Spektrofotometre instrument. The result of this the research showed that the compound which has the correlation toward bittertaste to the melon GMP was the calcium mineral with the TAV grade as 0,01 – 0,02, bitter amino acid TAV grade as 0,03 – 0,08, and total phenolic content flesh fruit TAV as 0,17 – 0,32 and total phenolic content pulp fruit TAV as 0,52 – 0,66 . The result of these three compounds after compared of each compounds, lounded that the phenolic content of pulp fruit has a hight degree as 0,52 – 0,66 and it showed the prediction of the compounds which has the most correlation towards the bitter taste upon the melon GMP is phenolic of pulp fruit.